Do Mobile Technology in the Classroom Really Improve Learning Outcomes? - Shazia Zaheer; Saad Masood Butt; Gnevasheva Vera Anatolyevna; Hosna Salmani (Institute of Advanced Engineering and Science, 2018)
This article aims to outline different pedagogical strategies with applications (apps) in the classroom. Every year the use of mobile devices like tablets and smartphones increases. At the same time, applications are being developed to meet this demand. It is therefore essential that educators investigate their use as an motivational technological medium that can possibly be used in the classroom. Apps can be used both as a source of information as well as a tool for creating material. Thus, this article will present the results of a study applying teaching strategies in different contexts. It therefore highlights the importance of mobile learning as a viable alternative in the classroom. In order to do so, there was a multiple case study in the undergraduate pedagogy program and a digital inclusion course for seniors, both offered in the first semester of 2017 at the Federal University of Rio Grande do Sul (UFRGS). Educational applications and examples of teaching strategies using apps were created in these classes. Educational applications offer the possibility to bring innovations to teaching practices, as well as new forms of communication, interaction and authorship, thus contributing to the process of teaching and learning.